Electrocoagulation for nitrate removal in groundwater of intensive agricultural region: a case study of Harran plain, Turkey - Yazici Karabulut, B.; Atasoy, A.D.; Can, Orhan Taner; Yesilnacar, M.I. (Springer Science and Business Media Deutschland GmbH, 2021)
This study focuses on the mechanism of Nitrate (NO3?) removal from aqueous solutions by electrocoagulation (EC) using aluminum (Al) and iron (Fe) electrodes and on the reduction of high nitrate levels in the groundwater of an arid/semi-arid region. Influence of initial pH, varying electrode material, inter-electrode distance, initial conductivity, and nitrate concentration over percentage removal of nitrate as well as energy consumption were all studied. The process was carried out by batch method at room temperature (25 °C). Tests were performed on a synthetic water sample prepared in the laboratory and ten samples collected from the Harran Plain region. According to the results of experimental studies, optimum experimental conditions were found to be with Al electrodes and initial pH = 6, run time = 210 min, current density = 2.31 A/m2, inter-electrode distance = 10 mm, and conductivity = 1000 µs/cm for removal of 80.1% nitrate (initial concentration = 250 mg/L). The energy consumption for experimental setup and real groundwater were 2.07 kWh/m3 and 1.925 kWh/m3, respectively. As the Al electrode distance was increased from 10 to 20 mm, the percentage of nitrate removal decreased from 80.1 to 62.3% because of the decrease in electrostatic attraction. It was found that Fe electrodes did not have a significant effect on nitrate removal (12.4%). The removal efficiency of Ugurlu groundwater that has the highest nitrate concentration was found to be 62.0% for Al electrode and 39.0% for Fe electrode. The Al-Al electrode combination used in the studies yielded better efficiency than the Fe–Fe electrode combination. It is thought that this method will also be applicable to regions with the same characteristics as the arid/semi-arid study region. © 2021, The Author(s), under exclusive licence to Springer-Verlag GmbH, DE part of Springer Nature.
Keywords: Electrocoagulation; Groundwater; Harran plain; Nitrate removal